Profil działalności technicznej ubezpieczycieli skandynawskich - Bożek-Węglarz, Sylwia (Profile of Operating Activity of Scandinavian Insurers, 2008)
The aim of this paper is a presentation of different aspects of operating activity insurance companies in Scandinavia for example Finland and Sweden. Life and non-life insurers' operating activity was evaluated using the ratios that measure the tendency for operating policy. Ratios of activity efficiency of Finnish and Swedish insurers' allowing for combined, loss, and expense ratios in non-life insurance have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 39-45